Energetic and Exergetic Analysis of a Solar Organic Rankine Cycle with Triple Effect Absorption System - Sharifishourabi, Moslem (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
As the population increases, the energy demand increases and this requires to develop new and alternative technologies such as wind, solar, biomass, and geothermal for meeting the demands. There was a significant increase in the study of multi-generation energy systems in the last decades, in order to decrease consumption of non-renewable energy sources and optimize more viable and economical energy production. A multi-generation system is a process used to produce three or more different outputs, such as hydrogen, electricity, cooling, hot water, heating, fresh air and water with the same input energy sources. In this thesis, a new multi-generation energy system is proposed based on solar energy. Solar energy is applied by feeding an Organic Rankine Cycle (ORC) which is then used to supply hot water to the buildings as well as electric current to the electrolyser with the aim of production hydrogen and also using in the building. A triple effect absorption system is utilized to produce cooling, heating, and dry air. A comprehensive thermodynamic analysis is defined, and the effects of various operating conditions and configurations on the output are analyzed. The results show that the system has an exergetic utilization factor of 0.6 and an energetic utilization factor of 2.61 based on generating electricity of 427kW. Also the energetic and exergetic COP of absorption chiller are determined to be 1.16 and 0.24, respectively. In the proposed system, the energetic and exergetic efficiency of Organic Rankine Cycle are 21.08% and 33.98, respectively. The extracted numbers from the system analysis in comparison with previous studies, validate the system performance under the defined initial parameters. So by analyzing the obtained results, it has become a necessity to decrease the system’s irreversibility and increase the energy and exergy efficiencies to reach a high efficient system. All modeling and thermodynamic analysis have been done by Engineering Equation Solver (EES) software. Keywords: Absorption System, Multi-generation System, Energy, Exergy, Efficiency

Öz: Dünya nüfusu arttıkça, enerji talebi artmakta ve gerekli rüzgar, güneş, biyokütle ve jeotermal gibi yeni alternatif enerji kaynakları ön plana çıkmaktadır. Ekonomik fizibilitesi daha uygun olan daha uygun ve ekonomik enerji üretimini optimize etmek için yenilenebilir olmayan enerji kullanımını azaltmak için kayda değer sayıda çalışmalar yapılmıştır. Çok üretimli sistemler tek bir enerji kaynağndan, hidrojen, elektrik, soğutma, sıcak su, ısıtma, taze hava ve su gibi üç veya daha çok çıktının sağlandığı bir işlemdir. Bu tezde, güneş enerjisine dayalı çok üretimli yeni bir enerji sistemi önerilmektedir. Güneş enerjisi hidrojen üretimi amacıyla elektroliz kullanarak ve aynı zamanda binada kullanmak için bina ve elektrik sıcak su temini için bir Organik Rankine Çevrimini (ORC) beslemek için uygulanmıştır. Bir üçlü etkili abzorpsiyonlu sistem, soğutma ısıtma ve kuru hava üretmek için kullanılmıştır. Kapsamlı bir termodinamik analizi tanımlanmş olup çıktılar üzerinde farklı işlem koşulları, etkileri ve konfigürasyonları analiz edildi. Sonuçlara göre sistemin elektrik üretim kapasitesi 427kW olduğunda, ekserjetik kullanım faktörü 0.6 olup enerji kullanım faktörü ise 2.61 dir. Ayrıca soğutma sistemine ait enerji ve ekserji COP değerleri sırasıyla 1.16 ve 0.24 olarak belirlenmiştir. Önerilen sistemde, enerjik ve ekserjetic verim Ornagik Rankine Cevriminde sirasiyla %21.08 ve %38.98 dir. Sistem analizlerinden elde edilen değerler daha önceki çalışmalarla karşılaştırıldığnda sonuçların geçerli olduğu kanaatine varılmıştır. Ayrıca analizden elde edilen sonuçlarda, irreversibilitileri azaltmak ve verimlilikleri artırmak sureti ile sistemi optimize etmek bir gereklilik olmuştur. Bütün modelleme ve termodinamik analizler Engineering Equation Solver (EES) yazılımı kullanılarak yapılmıştır. Anahtar Kelimeler: Önleme Sistemi, Çoklu nesil Sistemi, Enerji, Ekserji, Verimlilik.
Master of Science in Mechanical Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Mechanical Engineering, 2016. Supervisor: Prof. Dr. Uğur Atikol.
Keywords: Mechanical Engineering; Solar energy; Power resources; Sustainable development; Absorption System; Multi-generation System; Energy; Exergy; Efficiency